2021
DOI: 10.1039/d1fo01558c
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect and underlying mechanism of Rhus chinensis Mill. fruits on dextran sulphate sodium-induced ulcerative colitis in mice

Abstract: The purpose of this research was to explore the preventative effect of the 80% ethanol extract of Rhus chinensis Mill. fruits on dextran sulfate sodium (DSS)-induced colitis in mice and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In previous studies, tannin [ 15 ], flavonoids [ 9 ], carbohydrates [ 13 ] and other chemicals were found in the secondary metabolites of various extracts of water caltrop husk [ 13 , 15 ]. These chemicals are also known as lifetime metabolites of plants, and have been reported with some bioactivities, such as improving diabetes [ 19 ], cancer [ 22 , 23 ], gastric ulcer [ 24 ], alcoholic fatty liver disease [ 25 ], nonalcoholic fatty liver disease [ 26 ] and colitis [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, tannin [ 15 ], flavonoids [ 9 ], carbohydrates [ 13 ] and other chemicals were found in the secondary metabolites of various extracts of water caltrop husk [ 13 , 15 ]. These chemicals are also known as lifetime metabolites of plants, and have been reported with some bioactivities, such as improving diabetes [ 19 ], cancer [ 22 , 23 ], gastric ulcer [ 24 ], alcoholic fatty liver disease [ 25 ], nonalcoholic fatty liver disease [ 26 ] and colitis [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various proinflammatory cytokines, such as, tumor necrosis factor-alpha (TNF-α) and interleukins (ILs) get overexpressed under the influence of activated mast cells and innate immune response at the site of inflammation. , These mediators play a crucial role in the pathogenesis of UC and other related inflammatory diseases. , The exaggerated inflammatory responses adversely affect the colon homeostasis that leads to the development and progression of disease. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, further studies are needed to investigate the phenolic compounds that play a major role in DDC-induced cholestasis, and the structure-activity relationships and synergies between these compounds, which will contribute to a better understanding and application of dietary phenolic substances to prevent DDC-induced cholestasis. Zhang et al [ 48 ] studied the effect of ethanol extracts of RCM fruits on dextran sodium sulfate-induced colitis in C57 mice at a dose of 400 and 800 mg/kg b.w., the results showed that these two doses had no toxic effect on mice, and could exert good antioxidant and anti-inflammatory effects. Therefore, the selection of concentration in this paper was consistent with Zhang et al Moreover, preliminary conversion [ 49 ] demonstrated that the intake of 400 and 800 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%